Egypt and Canaan during the Middle Bronze Age - Bietak, Manfred (1991)
The existence of Middle Bronze Age remains within the fine stratification of Tell el-Dabʿa brings about the possibility of a new direct link to Egyptian cultural sequence and absolute chronology. Recent seriation studies of Egyptian pottery also add to the precision of dating by allowing cross links with other well-dated assemblages in Egypt. The evaluation shows that hitherto popular schemes for Palestinian chronology have to be lowered in relative and absolute terms. The result offers a very promising tool for reinterpretation of the historical context of the Middle Bronze Age world in connection with reconstruction of trade and cultural clusters.